ANALYSIS OF THE IMPLEMENTATION OF ACCOUNTING LEASING AT FEDERAL INTERNATIONAL FINANCE MANADO - Setiawan, Iksan; Alexander, Stanly W. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Application of Accounting leasing the leasing company is a system that is controlable and used as a company's financial statements for which subsequently became a reference in strategic decision making by companyâ€™s management. This study aims to determine the application of lease accounting at PT. Federal International Finance (FIF) a to determine the harmonization of the application of Â lease accounting with SFAS No. 30 of 2011 about leasing. Source of data used are secondary data original from PT. Federal International Finance. The analytical method used is descriptive. The results showed that the adoption of lease accounting is in accordance With SFAS No. 30 of 2011 about lease, It can be seen from the provisions of the lease contract letter to the company stating the existence of the option for the lessee upon expiration of the lease, as such term is classified in one of the criteria for a capital lease. Finance managers should use direct methods when performing financial leasing transaction records, because through this method,companies can have better revenues compase to the operaly lease method. Keywords: application, leaseaccounting, accounting standards